m6A-modified lncRNA GAS5 promotes M1-polarization of microglia in alcohol use disorder - Shuang Zhu; Peng Wang; Jian Hu (Brain Research Bulletin)
Long noncoding RNA (lncRNA) are essential for modulating the onset and progression of alcohol use disorder (AUD). In this study, we investigated the molecular pathways through which lncRNA may contribute to AUD development. We assessed the expression levels of long noncoding RNA GAS5 (lncRNA GAS5) and microRNA-136–5p (miR-136–5p) in AUD tissue samples and cell lines using reverse transcription-quantitative polymerase chain reaction. Detection of GAS5 N6-methyladenosine (m6A) modifications, facilitated by alkylation repair homolog 5 (ALKBH5), was performed using RNA immunoprecipitation and RNA pull-down assays. The effect of GAS5 on the functionality of SH-SY5Y cells was evaluated using CCK-8 and Transwell assays. Our findings showed high levels of GAS5 expression in both AUD tissues and cell lines. Overexpression of GAS5 decreased the migratory capability of SH-SY5Y cells, whereas silencing GAS5 increased this ability. Bioinformatics analyses predicted a relationship between expression levels of miR-136–5p and GAS5, which was subsequently confirmed using dual-luciferase reporter assays. Additionally, we discovered that GAS5 acts as a sponge for miR-136–5p, leading to the upregulation of ATF2. Elevated levels of ATF2 are associated with M1 microglial polarization. In summary, m6A-modified GAS5 may influence the M1 polarization of microglia via the miR-136–5p/ATF2 pathway. Statistical evaluations were performed using GraphPad Prism V8.0, employing the student's t-test for comparisons between two groups, assuming a normal distribution and equal variances. When variances were unequal, but normality was maintained, the corrected Student's t-test was applied. The non-parametric Wilcoxon rank-sum test was used to analyze non-normally distributed data, and one-way ANOVA was used to compare three or more groups. Independent replication was ensured in the studies, with each experiment repeated at least three times and statistical significance was set at P < 0.05.